Objectives Of Efl Instruction With Islamic Perspectives - Kalayo Hasibuan Hasibuan; Larissa Yukika Yulanda Putri Putri; Meydhisa Adelia Putri Putri; M.Ikhfan Alfattah Alfattah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study explores the objectives of English as a Foreign Language (EFL) instruction from an Islamic perspective, emphasizing the integration of language learning with spiritual and moral development. It highlights how English language education can serve as a medium for da’wah, international communication, the reinforcement of Islamic values, and the cultivation of critical and analytical thinking rooted in Islamic teachings. Using a library research method, this study analyzes a wide range of literature related to Islamic education, language pedagogy, and value-based curriculum development. The findings reveal that EFL instruction, when aligned with Islamic principles, not only enhances linguistic competence but also contributes to character building and global engagement without compromising religious identity. This integration enables students to communicate ethically, reflect on global issues through an Islamic lens, and represent Islamic values in diverse cultural settings. Thus, the study advocates for a holistic and faith-conscious approach to EFL that prepares students to be morally grounded and intellectually capable global citizens.